If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + n + -1 = 11 Reorder the terms: -1 + n + n = 11 Combine like terms: n + n = 2n -1 + 2n = 11 Solving -1 + 2n = 11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2n = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 2n = 11 + 1 2n = 11 + 1 Combine like terms: 11 + 1 = 12 2n = 12 Divide each side by '2'. n = 6 Simplifying n = 6
| 14(6-2x)=x | | 7a+a=80 | | 8(3-2x)=x | | 8(4-2x)=x | | 9(3-2x)=x | | 9(4-2x)=x | | 6x-30=x+5 | | 3x+35=4x+35 | | (5x-4)/3-5(7+6x)/8=7 | | 32-4x=2x | | 32-4x=7x | | 32-4x=6x | | 2X+5=13+4X | | a/8=13 | | 32-4x=6x+22 | | n-11=25 | | 2w+8x-11y+7w+4x+4y= | | 9x+6=3x-12 | | n/4+10 | | h-5=3*7 | | n-5=19 | | n+33=52 | | 6x-2x=12-4 | | 211-5x=40x+21 | | 5-10x=59-31x | | ln*5*X=3 | | 21/7+87/9(4+9) | | y(y+2)=3 | | 2(y-1)=4x+5 | | 4x=10x-24 | | 2(7b-1)33=19b | | 48-6x=21x+15 |